The Doctrinal Foundations of the Change in U.S. Foreign Policy During Trump’s Presidency: Mexico and Canada - Ilya A. Sokov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. The research’s subject is the foreign policy’s theoretical foundations of D. Trump’s presidential administration in 2016–2020, which consist in changing the principles’ use of American liberal internationalism to the conservative nationalism’s principles under the motto which is called “Make America Great Again”. The theoretical approaches’ basis of intergovernmental interaction in the field of politics, economics and migration is considered on the example of relations between the United States, Canada and Mexico. The work’s purpose is to identify the doctrinal basis of D. Trump administration’s foreign policy and the impact of the adopted foreign policy settings on changes in intergovernmental interaction in the international arena.